2014
DOI: 10.1073/pnas.1406694111
|View full text |Cite
|
Sign up to set email alerts
|

Shigella reroutes host cell central metabolism to obtain high-flux nutrient supply for vigorous intracellular growth

Abstract: Shigella flexneri proliferate in infected human epithelial cells at exceptionally high rates. This vigorous growth has important consequences for rapid progression to life-threatening bloody diarrhea, but the underlying metabolic mechanisms remain poorly understood. Here, we used metabolomics, proteomics, and genetic experiments to determine host and Shigella metabolism during infection in a cell culture model. The data suggest that infected host cells maintain largely normal fluxes through glycolytic pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
76
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 38 publications
19
76
0
Order By: Relevance
“…We also showed specific bacterial metabolism compared to two important mammalian cell lines, but this may not be representative of other cell types that may be encountered in vivo . However, our work is consistent with in vitro studies of other bacterial species, such as Shigella, have shown similar increased acetate production as a consequence of infection 38 .…”
Section: Discussionsupporting
confidence: 92%
“…We also showed specific bacterial metabolism compared to two important mammalian cell lines, but this may not be representative of other cell types that may be encountered in vivo . However, our work is consistent with in vitro studies of other bacterial species, such as Shigella, have shown similar increased acetate production as a consequence of infection 38 .…”
Section: Discussionsupporting
confidence: 92%
“…In line with a previous study of HeLa cells 26 , we found that S. flexneri induced acetyl-CoA production in THP-1 cells, suggesting that, in both cases, S. flexneri supports its own rapid intracellular growth and replication by manipulating the central metabolism of the host cell (Fig. 4g).…”
supporting
confidence: 92%
“…Moreover, the identification of genes involved in pyruvate catabolism (PDHB, DLAT, CS, PDHA1, MPC1, MPC2; Fig. 1f) echoed the rerouting of carbon flux by S. flexneri observed in HeLa cells 26 , which supports the rapid growth of these bacteria in this host. Intriguingly, key components of the NLRC4 and NLRP3 inflammasomes (AIM2, CASP1, NLRC4, NLRP3, GSDMD, and NAIP) that are activated by S. flexneri T3SS effectors MxiI 17 , IpaB 27 , and IpaH7.8 28 in macrophages were identified as negative hits in our genome-wide CRISPR screens (i.e., a gene whose knockout or knockdown shortened THP-1 cell survival) (Fig.…”
supporting
confidence: 60%
“…4). We calculated the doubling time of S. flexneri to be 47.1 Ϯ 6.7 min, which is slightly higher than doubling times reported for S. flexneri grown in metastatic Henle-407 or HeLa cells (28,49,50).…”
mentioning
confidence: 59%
“…The interaction between Shigella and host metabolism is inherently difficult to discern. Despite being able to replicate to a high cell density in the HeLa cell cytosol, host metabolism remains relatively stable, and host cells retain their energy charge during infection (7,28). And while overall amino acid levels remain steady in infected HeLa cells, HeLa cells exhibit signs of amino acid starvation during Shigella infection (60).…”
Section: Discussionmentioning
confidence: 99%